Vertical farm. New architectures and cities from the forms of agriculture - Sara Basso; Adriano Venudo; Thomas Bisiani; Pierluigi Martorana (Agathón)
The paper investigates the convergence between nature and architecture, analysing the phenomenon of vertical farms as an architectural manifestation of specific contemporary trends. These high-rise buildings are functional for agriculture while also exhibiting sustainability features, such as the reduction of supply chains and land consumption. The issue is articulated through four areas: the origin of the tall building as a symbolic expression and its contemporary evolution; above-ground agriculture in relation to classical macroeconomic categories since the 1700s; and three case studies of experimental vertical farms (Skyfarm, Farmscraper and Farmhouse), interpreted as possible origins of new architectural types. In conclusion, a critical analysis of the potential urban impacts of vertical farms is conducted, based on the concept of the right to food.